Autism Spectrum Disorder: general aspects and concerns about Brazilian politics - Marco Aurelio M Freire; Stanley Bittar (Hospital de Clínicas de Itajubá, 2023)
Autism Spectrum Disorder (ASD) encompasses a highly variable set of neurodevelopmental disorders with early onset and non-degenerative pattern. According to the World Health Organization's International Classification of Diseases (11th Revision), ICD-11, ASD is characterized as "persistent deficits in the ability to initiate and to sustain reciprocal social interaction and social communication, and by a range of restricted, repetitive, and inflexible patterns of behaviour, interests or activities that are clearly atypical or excessive for the individual's age and sociocultural context."